Ignition performance of TiO2 coated boron particles using a shock tube. Issue 5 (1st March 2022) - Deshmukh, P.R.; Kim, Yongjun; Shin, Weon Gyu
Abstract: This study coated the surface of irregularly shaped 5-μm boron particles with TiO2 nanoparticles to improve the ignition performance of the boron. A simple and inexpensive chemical method was used to coat the surface of boron with TiO2 . Five different samples of boron coated with TiO2 nanoparticles were obtained by varying the concentration of Ti precursor. Surface structures were analyzed using different characterization techniques, which showed the formation of nanocrystalline TiO2 nanoparticles over the boron surface. The nanoparticles of TiO2 were well dispersed over the boron surface, and exhibited strong interfacial contact with the boron. The oxidation of boron and boron coated with TiO2 was analyzed by thermogravimetric technique in an air atmosphere from room temperature to 1000 °C. Results revealed that the oxidation of boron started at a temperature approximately 162 °C lower after coating with TiO2 . The ignition behavior of the boron and boron coated with TiO2 particles was studied using a shock tube. The results of the shock tube experiments demonstrated the TiO2 coated boron had a shorter ignition delay time than the bare boron. An approximate 35% reduction was observed in the ignition delay time of boron after coating with TiO2 nanoparticles, showing its potential value in high energy density fuels.